A Plan for the Definition of Endowment Income - Litvack, James M; Malkiel, Burton G.; Quandt, Richard E. (American Economic Review, 1974)
The conventional financial rule under which institutions deriving at least part of their income from securities have traditionally operated is that dividends and interest may be spent but not capital gains. In recent years the conventional wisdom has been attacked, partly on the grounds that it ill serves the institutions in question. ' The purpose of this paper is (a) briefly to examine the principal reasons for employing a definition of endowment income different from that implied by the conventional spending rule, (b) to discuss the implementation of the new definition which was designed at Princeton University and contrast it with some alternatives, and (c) to indicate the new spending rule's operation with the aid of some sampling experiments.